A blue-emitting Sc silicate phosphor for ultraviolet excited light-emitting diodes. Issue 41 (5th August 2015) - Wang, Qian; Zhu, Ge; Xin, Shuangyu; Ding, Xin; Xu, Ju; Wang, Yuansheng; Wang, Yuhua
Abstract : A series of phosphor BaSc2 Si3 O10 :Eu 2+ was synthesized, which exhibited strong absorption in the near ultraviolet range and gave abnormal blue emission. Abstract : A blue-emitting phosphor BaSc2 Si3 O10 :Eu 2+ was synthesized using the conventional solid-state reaction. The crystallographic occupancy of Eu 2+ in the BaSc2 Si3 O10 matrix was studied based on the Rietveld refinement results and the photoluminescence properties. BaSc2 Si3 O10 exhibits blue emission ascribed to 3 T2 – 1 A1 and 3 T1 – 1 A1 charge transfer of SiO4 4− excited by 360 nm. All the phosphors of BaSc2 Si3 O10 :Eu 2+ exhibit strong broad absorption bands in the near ultraviolet range, and give abnormal blue emission upon 330 nm excitation. The abnormal phenomenon was explored in detail through many pieces of experimental evidence. The concentration of Eu 2+ is optimized to be 3 mol% according to emission intensity and the quenching mechanism is verified to be a quadrupole–quadrupole interaction. The CIE coordinates of BaSc2 Si3 O10 :0.03Eu 2+ are calculated to be (0.15, 0.05) and BaSc2 Si3 O10 :0.03Eu 2+ shows similar thermal stability to commercial BaMgAl10 O17 :Eu 2+ .